PERJUANGAN SULTAN MAHMUD RI’AYAT SYAH MELAWAN BELANDA DITINJAU DARI ASPEK STRATEGI PEPERANGAN - Anwar, Syaiful (Sejarah dan Budaya: Jurnal Sejarah, Budaya, dan Pengajarannya, 2021)
Sultan Mahmud Ri'ayat Syah was a king with the title "Yang Dipertuan Besar Riau-Lingga-Johor-Pahang Kingdom", who led his kingdom to fight against the Dutch troops who attacked his kingdom. This research analyzes his struggle from the aspect of warfare strategy. This research is a qualitative research, using the method of Biographical History Research, to dig deeper into his superiority in leading the war series. The theory used is strategy theory and several other relevant theories. Data was collected using literature study techniques, and then analyzed and interpreted so that they have the expected meaning. From the discussion it was found that his decision to fight, move the defense area, and carry out a sea guerrilla war, was very precise and effective, so that he achieved a series of victories and his kingdom could last quite a long time.